Predicting Repeat and Total Visits to a Destination Using Simulation Modeling Through Time - Assaker, Guy (2012)
Previous literature has shown that important variations exist over time regarding the extent to which visitors make return trips to tourist destinations. This paper provides an analytical framework to account for time discrepancies in behavior and helps predict repeat visits to a destination at different time points. The authors carried out an empirically validated three-parameter Weibull distribution and a 50-period numerical simulation exercise to illustrate ways in which the pattern of repeat visits affects total visitors through time. Several scenarios representing different distribution parameters and different intensities of initial trips are illustrated. Implications for destination managers and future research extensions are suggested